Use of the Hospital Anxiety and Depression Scale and the Taiwanese Depression Questionnaire for screening depression in head and neck cancer patients in Taiwan - Lee Y; Wu YS; Chien CY; Fang FM; Hung CF (Neuropsychiatric Disease and Treatment, 2016)
Yu Lee,1 Yi-Shan Wu,1 Chih-Yen Chien,2 Fu-Min Fang,3 Chi-Fa Hung1 1Department of Psychiatry, 2Department of Otolaryngology, 3Department of Radiation Oncology, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan, Republic of China Objective: The purposes of this study are 1) to estimate the prevalence of common mental disorders including depressive disorder in patients with head and neck cancer (HNC) at baseline and at the 6-month follow-up and 2) to test the validity of two self-reported questionnaires, the Hospital Anxiety and Depression Scale (HADS) and the Taiwanese Depression Questionnaire (TDQ), for screening depression in patients with HNC. Methods: Participants were recruited from the outpatient collaborative care clinic for HNC of a tertiary hospital in Taiwan between January 2010 and January 2011. Ninety-three patients with HNC were enrolled and assessed using the HADS, TDQ, and Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, fourth edition, Patient edition, at baseline and at the 6-month follow-up. Conventional validity indices of the HADS and TDQ were examined. Results: Our results showed that the validity of the TDQ was satisfactory and comparable to that of both the HADS depression subscale and the HADS total scale. The cutoff scores of the HADS and TDQ for screening possible depressive disorders were 8 and 15, respectively. The areas under the receiver operating characteristic curve of the HADS and TDQ were mean 0.975±0.015 and 0.966±0.019, respectively. Thirteen participants (14%) were diagnosed with depressive disorders at the 6-month follow-up, compared with 8.5% at baseline. Conclusion: Our results indicate that both the HADS and TDQ are valid instruments for screening depression in patients with HNC. Keywords: head and neck cancer, Hospital Anxiety and Depression Scale, Taiwanese Depression Questionnaire, validity, prevalence